2012
DOI: 10.1186/1472-6963-12-166
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting hospital stay in psychiatric patients: the role of active comorbidity

Abstract: BackgroundResearch on length of stay (LOS) of psychiatric inpatients is an under-investigated issue. In this naturalistic study factors which affect LOS of two groups of patients were investigated, focusing on the impact on LOS of medical comorbidity severe enough to require referral.MethodsActive medical comorbidity was quantified using referral as the criterion. The study sample consisted of 200 inpatients with the diagnosis of schizophrenia and 228 inpatients suffering from bipolar disorder (type I or II). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 48 publications
4
52
5
5
Order By: Relevance
“…However, we found that the diagnosis of bipolar affective disorder was associated with shorter duration of hospital stay. This finding is in contrast with previous studies [4,12,16]. While the explanation for this finding may not be known in the immediate, we theorized that time of onset of overt manic symptoms to presentation and admission in the hospital may be of shorter duration compared to Schizophrenia and Substance use disorders.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, we found that the diagnosis of bipolar affective disorder was associated with shorter duration of hospital stay. This finding is in contrast with previous studies [4,12,16]. While the explanation for this finding may not be known in the immediate, we theorized that time of onset of overt manic symptoms to presentation and admission in the hospital may be of shorter duration compared to Schizophrenia and Substance use disorders.…”
Section: Discussioncontrasting
confidence: 56%
“…Nowadays, longer hospital stay may imply poor mental health care and support in the community. Reduction of length of admission has been associated with less expenditure and successful treatment in the community [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of Douzenis et al's (2012) study are interesting and highlight the importance of addressing physical health problems in people with severe mental illness. It is important to note that the study was based on an inpatient sample in Greece where the provision of comprehensive community-based mental health care may not have been available.…”
Section: Predictors Of Length Of Staymentioning
confidence: 99%
“…One study focused on the impact of medical comorbidity on length of stay (Douzenis et al 2012). Two of the hypotheses tested aimed to examine whether severe comorbidity requiring referral in patients with schizophrenia and bipolar disorder would affect length of stay and what factors were associated with it.…”
Section: Predictors Of Length Of Staymentioning
confidence: 99%